Migraine improvement correlates with posterior cingulate cortical thickness reduction - Amaral, Vanise C. G.; Tukamoto, Gustavo; Kubo, Tadeu; Luiz, Ronir Raggio; Gasparetto, Emerson; Vincent, Maurice B. (Arquivos de Neuro-Psiquiatria, 2018)
Objective The main goal of this study was to correlate migraine improvement, after prophylactic therapy, with cortical thickness changes.Methods Cortical thickness maps were obtained with magnetic resonance imaging (MRI) from 19 patients with migraine before (first scan) and after (second scan) prophylactic treatment, and these were compared with controls using the FreeSurfer MRI tool. Cortical changes were correlated with the headache index (HI).Results Anincrease incortical thickness was found in the right cuneus and precuneus, somatosensory and superior parietal cortices in both patient scans, compared with the controls. No changes were observed in the left hemisphere. Following correction for multiple comparisons, no areas changed from the first to the second scan. Regression analysis showed a significant negative correlation between the HI improvement and cortical thickness changes in the left posterior cingulate, a region involved with nociception and, possibly, the development of chronic pain.Conclusion There were changes in cortical thickness in patients with migraine relative to controls in areas involved with vision and pain processing. Left posterior cingulate cortical changes correlated with headache frequency and intensity.
Keywords: migraine disorders; magnetic resonance imaging - FreeSurfer; prophylactic treatment